A new genus of calcareous sponge discovered in the Caribbean Sea: Bidderia gen. nov. (Porifera, Calcarea, Calcinea) - Lopes, Matheus V.; Cóndor-Luján, Báslavi; Azevedo, Fernanda; Pérez, Thierry; Klautau, Michelle (Zootaxa, 2018)
Calcareous sponges from the Lesser Antilles were recently inventoried and several specimens morphologically resembling species of the genus Ascoleucetta were collected. Morphological and molecular (C-LSU and ITS) analyses indicated that these specimens from the Lesser Antilles constituted a new genus. They lack the conspicuous and very characteristic ornamentation of the inhalant apertures found in two out of three species of Ascoleucetta, including the type species A. compressa. In the molecular analyses, the specimens clustered as an independent lineage, distant from the clade of A. compressa. Based on these results, we decided to erect a new genus, Bidderia gen. nov., whose type species is Bidderia bicolora gen. nov. sp. nov. Considering this new discovery, we are proposing to transfer the species A. amitsba to the genus Bidderia gen. nov. and to rediagnose Ascoleucetta.